Cell adhesion molecules in subretinal fluid: Soluble forms of VCAM-1 (vascular cell adhesion molecule-1) and L-selectin - (:unkn) unknown (SPRINGER, 1998)
Purpose: In this study we investigated the presence of soluble VCAM-1 and soluble L-selectin-1 in subretinal fluids (SRF) of patients suffering from rhegmatogenous retinal detachment . Method: Subretinal fluids were collected from drainage sclerotomies during surgery from 27 patients with rhegmatogenous retinal detachment complicated by proliferative vitreoretinopathy (PVR) or uncomplicated retinal detachment. Levels of sVCAM-1 and sL-selectin-1 were quantified with ELISA. Results: The mean +/- SEM values of sVCAM-1 and sL-selectin-1 were 222.2 +/- 81 ng/ml and 171.7 +/- 42.1 ng/ml, respectively. The concentrations of sVCAM-1 in patients with Grade C PVR (498.2 +/- 170 3 ng/ml) were significantly different from those with Grade B PVR (45.6 +/- 16.5 ng/ml) and uncomplicated retinal detachments (19.4 +/- 12.3 ng/ml). SVCAM-1 concentration in detachments which had been present for more than 8 weeks was 738.8 +/- 431 ng/ml, significantly higher than the levels in detachments of shorter duration (132.4 +/- 47.7 ng/ml). sL-selectin-1 level in Grade C PVR (291.6 +/- 92.8 ng/ml) was higher than in uncomplicated retinal detachments (72.8 +/- 13.5 ng/ml). Significantly elevated levels of sL-selectin-1 were observed in detachments lasting more than 8 weeks (605 +/- 151.1 ng/ml) compared to those of shorter duration (96.3 +/- 13.1 ng/ml). Conclusion: The present study supports growing evidence that these cell adhesion molecules are involved in the inflammatory process during the development and progression of PVR.
Keywords: subretinal fluid; rhegmatogenous retinal detachment; proliferative vitreoretinopathy; cell adhesion molecules; vascular cell adhesion molecule-1; L-selectin; PIGMENT EPITHELIAL-CELLS; MASSIVE PERIRETINAL PROLIFERATION; SYSTEMIC LUPUS-ERYTHEMATOSUS; PERI-RETINAL PROLIFERATION; EPIRETINAL MEMBRANES; ENDOTHELIAL-CELLS; RHEUMATOID-ARTHRITIS; CHEMOTACTIC FACTORS; VITREORETINOPATHY; DETACHMENT